A stochastic geometry-based performance analysis of a UAV corridor-assisted IoT network - Armeniakos, Harris K.; Maliatsos, Konstantinos; Bithas, Petros S.; Kanatas, Athanasios G. (Frontiers in Communications and Networks, 2024)
The exploitation of Unmanned Aerial Vehicles (UAVs) in enhancing network performance in the context of beyond fifth-generation (5G) communications, has proven a variety of benefits as compared to terrestrial counterparts. Besides, they have been largely conceived to have a central role in data dissemination to Internet of Things (IoT) devices. In the proposed work, a novel stochastic geometry unified framework is proposed to study the downlink performance in a UAV-assisted IoT network which integrates both UAV-base stations (UAV-BSs) and terrestrial IoT receiving devices. The framework builds upon the concept of the aerial UAV corridor, which is modeled as a finite line above the IoT network and the one-dimensional (1D) binomial point process (BPP) is employed for modeling the spatial locations of the UAV-BSs in the aerial corridor. Subsequently, a comprehensive SNR-based performance analysis in terms of coverage probability, average rate, and energy efficiency is conducted under three association strategies, namely the n-th nearest selection scheme, the random selection scheme, and the joint transmission coordinated multi-point (JT-CoMP) scheme. The numerical results reveal valuable system-level insights and trade-offs and provide a firm foundation towards the design of UAV-assisted IoT networks.